Leo Elders, Santo Tomás de Aquino hoy y otros estudios, edc. de la Sociedad Tomista Argentina, Buenos Aires, 1989, 78 pp - Donadío Maggi de Gandolfi, María C. (1990)
Fil: Donadío Maggi de Gandolfi, María C. Pontificia Universidad Católica Argentina; Argentina